Errors of Class VIII Junior High School Students in Solving Mathematical Communication Problems Based on the Newman Procedure - Linda Anggraini; Shinta Wulandari; Nurmala Nurmala (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Mathematical communication skills are the main capital in solving math problems. Mathematical communication skills help students in conveying ideas or solutions to a mathematical problem in the form of oral, written, and picture. The research objective is to identify student errors in solving mathematical communication problems. The type of research is descriptive qualitative so that the researcher is the main instrument. Technical data analysis in this research is descriptive qualitative data analysis technique of Miles and Huberman model with stages of data reduction, data presentation, conclusion drawing and verification. The data reduction stage aims to select, focus, discard unnecessary data and simplify raw data from the results of student error analysis. The research subjects were students of class VIII A SMP Negeri 2 Tanjung Palas Utara. The research showed that the students did not make reading errors but made mistakes in understanding, transforming, processing skill, and solving mathematical communication problems.